CAN PANDEMICS BE PREVENTED? WASTEWATER-BASED EPIDEMIOLOGY - Hernández, Elizabeth Velástegui (2022)
In this opinion article, the potential of the study of wastewater as an epidemiological predictor of future public health emergencies is analyzed. The detection of SARS-CoV-2 preliminary to the manifestation of clinical outbreaks in urban wastewater; and, the correlation between certain biological markers with intrinsic characteristics of the population allows us to elucidate that their analysis could be used as an early warning of the appearance of future public health emergencies. According to various predictions, humanity will face several health crises in this century derived from climate change and anthropogenic pollution. The application of omics tools in the analysis of wastewater allows to detect modifications in the patterns of pathogenic microorganisms, therefore, it is necessary to optimize methodologies that allow the application of these technologies as epidemiological tools at a global level